Evaluation of Mechanical Properties of Concrete Containing Silica Fume from a Local Source in Pakistan: Properties of Concrete Containing Silica Fume from a Local Source in Pakistan - Firdous, Rafia; Ilyas, Usman; Akram, Affifa; Adnan, Maryam (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
Concrete is one of the most commonly used construction materials with cement being its main ingredient. Since the construction industry is expanding rapidly, the cost of cement used in concrete is also increasing. In order to meet its growing demand and address the adverse effects on account of its production process, alternate cheap materials are needed to be developed. Silica Fume is a well-known pozzolanic material which when partially replaced with cement, enhances the mechanical and chemical properties of concrete and mortar. In present experimental research, compressive strength and modulus of rupture of concrete containing silica fume as secondary cementitious material have been evaluated. Silica fume was obtained from a local source in Pakistan. The incorporation of silica fume resulted in higher water demand in comparison with control concrete mixture. Replacement of cement with silica fume was by weight of cement in ratios of 0%, 10%, 15% and 20%. The incorporation of silica fume improved the later-age strength as compared to early-age strength. It was also noted that the highest compressive strength and flexural tensile strength have been achieved by 15% replacement of silica fume with cement at all ages.